Micromechanical Studies of 4n Gold Wire for Fine Pitch Wirebonding - M. Yunoh, M.F.; Abdullah, S.; Jalar, A.; Rosle, M. F.; Radzi, S.A. (Journal of Science and Technology, 2010)
This study focuses towards typical micromechanical properties such as strength, yield point, Young’s Modulus, strain, shapes of fracture end and element analysis, atomic percentage of Ca of 4N gold (Au) wire using microstructures and composition observation, micro-tensile test and depth sensing indentation technique. A series of micro-tensile test were performed with different strain rate values of 10Ëš-10-4 min-1 on to a 25.4 μm diameter plain gold wire. The nanoindentation with 20 mN maximum load was indented on a near fracture end of a gold wire specimen, for which this test was carried out after the micro-tensile test. The stress-strain curves were used to characterize the 4N purity gold wire. The shapes of fracture end of gold wire after micro tensile test were carried out using Scanning Electron Microscopic (SEM). The finding showed that the mechanical properties of ultra-fine gold wire was in the proportional relationship with the increment of the strain rate value. It is suggested that micromechanical behaviour gave the effect for the wirebonding process in order to characterize the wire loop control and strengthen the wire loop to avoid the wire sweep.